ANALYSIS OF GENETIC STRUCTURE AND DIVERSITY IN INDIAN MUSTARD [BRASSICA JUNCEA (L.) CZERN & COSS.] ASSESSED BY SSR MARKERS - V. K. Singh; R. Avtar; Mahavir; N. Kumari; Manjeet; R. Kumar; R. S. Khedwal (Journal of Animal and Plant Sciences, 2022)
In present endeavors, the genetic diversity and Bayesian structure of 88 genotypes of Indian mustard procured from four different centers viz., ICAR-DRMR Bharatpur, ICAR-IARI New Delhi, CCS HAU Hisar and PAU Ludhiana were studied using 59 genomic SSR markers, and their genetic liaison was explored. A total of 209 repeatable alleles were detected by 59 SSR markers in a size range of 50-1000 bp with maximum (7) fragments intensified by BG6, BG32, BG46 and BG71 markers. The average value of PIC and the mean expected heterozygosity (He) value from all the polymorphic primers were 0.49 and 0.56, respectively, which is an indicative of the presence of ample amount of genetic diversity among Indian mustard genotypes. All the 88 genotypes were grouped into four distinct clusters based on Jaccard’s dissimilarity coefficients and UNJ (Unweighted Neighbour Joining) methods, however, three subpopulations were predicted by bayesian structure analysis at delK = 3. The PCoA (Principal Coordinate Analysis) revealed 20.95% and 10.85% of variation, respectively, with 31.80% of cumulative variation. The present work indicates the presence of considerable genetic diversity among the Indian mustard genotypes, which could be used in future breeding programmes for developing mustard cultivars and germplasm management purposes.
Keywords: Indian mustard; genetic diversity; bayesian structure; SSRs